2014
DOI: 10.1002/smll.201402933
|View full text |Cite
|
Sign up to set email alerts
|

Effective Gene Delivery into Human Stem Cells with a Cell-Targeting Peptide-Modified Bioreducible Polymer

Abstract: Stem cells are poorly permissive to non-viral gene transfection reagents. In this study, we explored the possibility of improving gene delivery into human embryonic (hESC) and mesenchymal (hMSC) stem cells by synergizing the activity of a cell-binding ligand with a polymer that releases nucleic acids in a cytoplasm-responsive manner. A 29 amino acid long peptide, RVG, targeting the nicotinic acetylcholine receptor (nAchR) was identified to bind both hMSC and H9-derived hESC. Conjugating RVG to a redox-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…BMMSCs are reluctant to accept gene transfection via using nonviral vectors without impacting the pluripotency or cell viability due to the variability in the cell subpopulation and the toxicity of many transfection methods, which frequently results in substantially low efficiencies [15][16][17][18]. Thus, clinical studies have been mostly limited to the non-transfected BMMSCs.…”
mentioning
confidence: 98%
“…BMMSCs are reluctant to accept gene transfection via using nonviral vectors without impacting the pluripotency or cell viability due to the variability in the cell subpopulation and the toxicity of many transfection methods, which frequently results in substantially low efficiencies [15][16][17][18]. Thus, clinical studies have been mostly limited to the non-transfected BMMSCs.…”
mentioning
confidence: 98%
“…This result was consistent with the combinations between the ligand and gene vector could enhance gene transfection of the gene delivery system. 37 This therapeutic effect suggested that siRNA might be carried into the cells in cysts and afterward accumulated to the lesion via the encapsulation of (CSO-PEI)HA. It is the (CSO-PEI)HA that facilitate the siRNA to deliver into the target sites.…”
mentioning
confidence: 99%
“…The ATS-9R/shFABP4 oligopeptide complex targeted mature adipocytes via binding to inhibitin and silencing of the targeted sequence peptide resulted in reduced lipidosis [ 82 ]. A 29-amino acid cell-binding peptide, RGV, conjugated to the redox-sensitive biodegradable dendrimer PAM-ABP, provided a low toxicity compound that increased transfection rates of both hMSC and hESC (about 60 and 50%, respectively) and retained expression of pluripotent stem cell markers [ 83 ]. Mannosylated CPP was bound to PEI to form the polymer Man-PEI1800-CPP, which was targeted at the mannose receptor on antigen-presenting cells (APC); its transfection rate was higher than 25KDa PEI but with lower toxicity, and in vivo experiments showed that this kind of nVGDS was mainly distributed in the epidermis and dermis [ 52 ].…”
Section: Non-viral Gene Delivery System Designmentioning
confidence: 99%